Linear relations between apple traits - Toebe,Marcos (2016)
ABSTRACT The study of linear associations between traits is critical for the selection or the indirect quantification of the interest traits. Thus, the objective of this research was to evaluate the linear relationships among traits of apple fruits, in ‘Royal Gala’ and ‘Fuji’ cultivars, at harvest and after cold storage. In this investigation, 120 fruits of ‘Royal Gala’ and 120 fruits of ‘Fuji’ at harvest and 120 fruits of ‘Royal Gala’ and 111 fruits of ‘Fuji’ after cold storage were evaluated. Morphological/productive (mass, longitudinal diameter, major and minor transverse diameters) and quality traits (firmness, total soluble solids, titratable acidity, juice content, ethylene production and respiration) were measured. In each cultivar (‘Royal Gala’ and ‘Fuji’) and time of evaluation (at harvest or after cold storage), the Pearson’s linear correlation coefficients among the pairs of traits and the canonical correlation among the groups of morphological/productive and of quality traits were calculated. At harvest, the apple fruits with higher mass had lower firmness and higher total soluble solids, regardless of the cultivar. After cold storage, the apple fruits with higher mass had higher total soluble solids and lower respiration, regardless of the cultivar, and higher juice content in the ‘Fuji’ cultivar.